Bird's-eye view perspective map of the Archduchy Austria under the Ens. Southern view near the surroundings of Vienna: Section IV. - Unknown:::Creator::::::::::::; Schweickhardt, Franz Xaver, 1794-1861 (author):::Contributor::::::::::::
Color bird's-eye perspective map of Vienna's environs to the south.